ПЕРСПЕКТИВИ ВИКОРИСТАННЯ ПАРКІВ ПРИРОДНО-ЗАПОВІДНОГО ФОНДУ БУКОВИНИ ДЛЯ ЗБАГАЧЕННЯ ЇЇ БІОРІЗНОМАНІТТЯ - Решетюк, О.В. (Національний лісотехнічний університет України, 2017)
The authors present the results of studying parks of the natural reserve fund in Bukovyna. They have made a typological classification and a comprehensive analysis of the categories of these security projects. Six historical stages of local chain parks formation wer exuded. We have found out that most of them were equipped during the Austro-Hungarian period (small parks of the combined type) in Viennese traditions. In the middle of the 20th century when significant reconstruction of park plantings was carried out, some of them were fixed in the collection block of the nature reserve fund. We have also discovered that in terms of the number of parks, the region is ahead of the average indicator in Ukraine, although these parks are smaller in size. It is established that the size of the parks plays an important role in their specialization and functioning; most of the parks of Bukovyna are monofunctional (43). The general tendency is the predominance of rural parks by number and urban – by area. The territorial division of parks was made: the majority is located in the Precarpathians region (31), in the Bukovyna Carpathians there are only 3 park-sights of garden and park art located on the border with the Precarpathians (Vyzhnytsky, Beregometsky, Krasnoilsky). It was rewealed that parks in Chernivtsi (45 %), Storozhynets (19.4 %) and Kitsman (7.8 %) occupy the largest share by the area. It is proved that the composition of plantations in Bukovyna parks is based on the local flora with a wide application of introducents (213 species and forms of tree plants from 37 families, 90 genus). It is determined that most introducents come from North America, Japan and China. The unique types of introducents have been discovered, which can become a source of enrichment of many dendrological collections of botanical gardens and arboretums. It is recommended to preserve deciduous species of aboriginal flora in planning parks if they don't violate the landscape composition. We have noted the necessity of cautious attitude towards introducents, polling conditions of their growth and weakening competition of aboriginal species. The results of the research have revealed the unique importance of collecting block objects in the formation of chain of protected objects in Bukovyna, because they can be widely used not only for health and recreation of citizens, but also for education and research. It is mentioned that parks subordinate to medical and educational institutions not only promote recreational and educational activities, but also keep collections better in conditions of limited accessibility and system monitoring.
Keywords: garden-park art; arboretums; botanical gardens; retrospective; introducents; park plantings; reserve fund